If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 + -20x = 0 Solving 45 + -20x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + -20x = 0 + -45 Combine like terms: 45 + -45 = 0 0 + -20x = 0 + -45 -20x = 0 + -45 Combine like terms: 0 + -45 = -45 -20x = -45 Divide each side by '-20'. x = 2.25 Simplifying x = 2.25
| k/7-8=-10 | | 8.9=x-9.5 | | -5v-10=50 | | 8t-12=4(2t-3) | | 3x-x^2=20 | | 6i+3=-7 | | P=14*(8/t) | | -8u-15=15 | | -25t+7t^2-12=0 | | 4(n+6)-2n=3(n+3)-11 | | 7+30x=20x+23 | | 5*(4-9*2)-2*(3*2+4)+7= | | 3w^6*v^9*2v^4*7w=0 | | 32=X-5 | | y=0.5+-1.5y+1 | | 64=l-4 | | 3w^6*v^8*2v^4*7w=0 | | 40/(-5) | | 250=9x-38 | | 6z-30= | | 21x^2+50xy-16y^2=0 | | -0.8n=40 | | Z/3=z—2 | | Y(x+1)-4(x+1)= | | -.125c=2 | | x+2x+3x+4=40 | | 16x=256/x | | 8-3x+7x=-12 | | 4x+40+3x=180 | | m=-1/2;(-4,7) | | (3-u)(3u-2)=0 | | 9ln(x+18)-6ln(x)= |